The Influence of Pancasila Values Understanding on Tolerance Behavior in Vocational School Students - Baihaqi, Muhammad Iqbal; Aini, Kusuma Dewi Nur (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2025)
This study aims to examine the influence of students' understanding of Pancasila values on their tolerance behavior at SMK Islam Kanigoro. A quantitative approach with a correlational design was employed, involving 100 students selected through simple random sampling. Data were collected using a questionnaire that assessed both the understanding of Pancasila values and tolerance behavior. The results of the validity test revealed that only one item was valid for measuring Pancasila understanding, while others required revision. The correlation analysis showed a significant positive relationship between understanding Pancasila values and tolerance behavior (r = 0.286, p = 0.004). However, the simple linear regression analysis indicated that understanding Pancasila only explained 8.2% of the variance in students' tolerance behavior. These findings suggest that while Pancasila education plays a role in fostering tolerance, other factors may also influence tolerance behavior. This research highlights the importance of refining educational instruments and suggests that future studies should explore additional variables that may contribute to tolerance. The study emphasizes the need for more comprehensive and interactive civic education programs to cultivate tolerance in diverse societal contexts.